Incidencia del arrendamiento financiero (leasing) y sus beneficios en la mejora de la gestión financiera y tributaria en las empresas de transportes del distrito de Trujillo: Transportes Joselito S.A.C. - Benitez Valdivia, Tatiana Isabel (2013)
This thesis develops the theme "Impact of Financial Lease (Leasing) and its benefits in improving financial management in the Business and Tax District Transport Trujillo: Transport Joselito S.A.C." The vision of this subject is to give the company an option to evaluate for future investment financing through Financial Leasing and its Application in the Freight Transport Companies, and thus determine whether this form of finance would help the company to have greater liquidity being able to provide a level of savings and contribute to the solution of potential problems possessing fixed assets, for this we used financial information from the company whose name Transport Joselito S.A.C. To complete this study will detail the benefits implicit negotiations accounting tax and other the Financial Leasing through practical application in the company Transport Joselito S.A.C. Finally, based on the analysis concludes that the financial leasing option is the best alternative for the acquisition of commercial vehicles, which are described more fully in the conclusions and recommendations described in the final part of this paper research.